Human Rights Defenders, an Obstacle in the Fight against Terrorism - Carrillo-Ballesteros, José Guillermo (DIXI, 2014)
After the terrorist attacks of September 11, 2001 in the United States, March 11, 2004 in Madrid and those in London on July 7 and 21 of 2005, the implementation of antiterrorist policies and strengthening of national security became the priority of states, and while legitimate and necessary, over time this deviated from its main objective and became the perfect “alibi” to enable many states to consolidate their repressive arsenal and strengthen their power. In the name of this struggle, it would seem that all abuses were justifid and the methods used soon gave rise to greater human rights violations. However, in this context of total repression, it has been the denunciations by human rights defenders that have revealed excesses and abuses of power. In doing so, they endanger themselves and their families, while suffring stigmatization and seeing their work criminalized. For many states, they thus become true obstacles in the fiht against terrorism.